Creating 'Partnership in iSupport program' to optimise family carers' impact on dementia care: a randomised controlled trial protocol - Lily Xiao; Ying Yu; Julie Ratcliffe; Rachel Milte; Claudia Meyer; Michael Chapman; Langduo Chen; Shahid Ullah; Alison Kitson; Andre Queiroz De Andrade; Elizabeth Beattie; Henry Brodaty; et al. (BMC, 2022)
Abstract Background The majority of people with dementia are cared for by their family members. However, family carers are often unprepared for their caring roles, receiving less education and support compared with professional carers. The consequences are their reduced mental and physical health and wellbeing, and that of care recipients. This study protocol introduces the 'Partnership in iSupport program' that includes five interventional components: managing transitions, managing dementia progression, psychoeducation, carer support group and feedback on services. This health services research is built on family carer and dementia care service provider partnerships. The aims of the study are to evaluate the effectiveness, cost-effectiveness and family carers' experiences in the program. Methods A multicentre randomised controlled trial will be conducted with family carers of people living with dementia from two tertiary hospitals and two community aged care providers across three Australian states. The estimated sample size is 185 family carers. They will be randomly assigned to either the intervention group or the usual care group. Outcomes are measurable improvements in quality of life for carers and people with dementia, caregiving self-efficacy, social support, dementia related symptoms, and health service use for carers and their care recipients. Data will be collected at three time points: baseline, 6 months and 12 months post-initiation of the intervention. Discussion This is the first large randomised controlled trial of a complex intervention on health and social care services with carers of people living with dementia in real-world practice across hospital and community aged care settings in three Australian states to ascertain the effectiveness, cost-effectiveness and carers' experiences of the innovative program. We expect that this study will address gaps in supporting dementia carers in health and social care systems while generating new knowledge of the mechanisms of change in the systems. Findings will strengthen proactive health management for both people living with dementia and their carers by embedding, scaling up and sustaining the 'Partnership in iSupport program' in the health and social care systems. Trial registration The Australian New Zealand Clinical Trials Registry (ANZCTR). ACTRN12622000199718 . Registered February 4th, 2022.